A Rare Disease With Rarer Presentation: A Case of Bardet-Biedl Syndrome Presented as End Stage Renal Disease Due To Glomerulonephritis - Rahman, Tahmidur; Hasan, Sayful; Huda, Md Nurul (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Bardet-Biedl Syndrome (BBS) is an autosomal recessive disease resulting from non-motile ciliopathyand presents with obesity, retinal abnormality, polydactyly, mental retardation, and genital abnormality. Renal involvement is not a frequent feature. The purpose of the study to reminding readers of this issue and emphasize the necessity for further research on how to deal within the best way. Case Presentation: A 17-year-old patient was admitted on 20th August 2023 at the Department of Nephrology, Chittagong Medical College Hospital, Chattogram with the features of BBS. According to clinical features and supportive investigation, he was diagnosed with Acute Kidney Injury (AKI) on Chronic Kidney Disease (CKD). The cause of CKD was probably due to Glomerulonephritis (GN). Renal replacement by hemodialysis was started along with other supportive medications. Conclusion: Bardet-Biedl syndrome is a non-curable disease, which may present with end stage of renal disease. JCMCTA 2024 ; 35 (1) : 176-179